ASPECTS OF SATISFACTION OF EMALINE CUSTOMERS - Dewi, Liliana; Siandika, Raynaldo Aditya (Jurnal Entrepreneur dan Entrepreneurship, 2018)
In order to achieve the objectives of the operations, Emaline needs to review the influence of product quality; which consists of aesthetics, durability, customer perceived quality, and serviceability, on the customer satisfaction of the company. The purpose of this study is to determine: the influence of aesthetics on customer satisfaction; the influence of durability on customer satisfaction; the influence of customer perceived quality on customer satisfaction; and the influence of serviceability on customer satisfaction. The samples in this research consist of 42 Emaline consumers under the business-to-consumer pattern who have made more than one purchase. Multiple Linear Regression is used as analysis technique in this study. Research results suggest that aesthetics, durability, customer perceived quality, and serviceability affect the customer satisfaction of Emaline.